2017
DOI: 10.18632/oncotarget.15374
|View full text |Cite
|
Sign up to set email alerts
|

Akirin2 promotes slow myosin heavy chain expression by CaN/NFATc1 signaling in porcine skeletal muscle satellite cells

Abstract: The objective of this study was to evaluate the effect of Akirin2 on slow myosin heavy chain (slow MyHC, MyHC I) gene expression and its molecular mechanisms. In this study, we showed that the protein expression of Akirin2 in pig slow oxidative Psoas major muscle is higher than that in fast glycolytic tibialis anterior muscle, suggesting that Akirin2 may play a role in myofiber typing. Knockdown of Akirin2 decreased the MyHC I expression and the calcineurin (CaN) activity, and also decreased the expressions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…29 Our previous studies demonstrated that Akirin2 promotes MyHC I expression. 8,9 Here, we showed that arginine upregulated Akirin2 expression. In addition, Akirin2 siRNA abolished arginine-induced MyHC I upregulation.…”
Section: ■ Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…29 Our previous studies demonstrated that Akirin2 promotes MyHC I expression. 8,9 Here, we showed that arginine upregulated Akirin2 expression. In addition, Akirin2 siRNA abolished arginine-induced MyHC I upregulation.…”
Section: ■ Discussionmentioning
confidence: 82%
“…It has been reported that Akirin2 promotes proliferation and differentiation of porcine skeletal muscle statellite cells . Our previous studies showed that Akirin2 regulates slow-twitch fiber expression by calcineurin (CaN)/nuclear factor of activated T cells c1 (NFATc1) signaling. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using satellite cells isolated from porcine muscles are also consistent with a role for Akirin2 in the proliferation and differentiation of these cells [53,77]. For example, siRNA knockdown of Akirin2 led to reductions in the mitotic marker phospho-histone H3 (PH3) and incorporation of EdU whilst overexpression of Akirin2 had the opposite effects [53].…”
Section: Akirin2mentioning
confidence: 68%
“…The proportion of oxidized myofibers can be increased by the addition of nutrients to animal diets [ 9 ]. There is much research investigating the modification of skeletal muscle satellite cell (SMSC) proliferation and differentiation to increase the formation of myofibers, to improve the quality of skeletal muscles [ 10 ].…”
Section: Introductionmentioning
confidence: 99%